Evaluation of Macular and Peripapillary Blood Flow in Response to Intraocular Pressure Reduction in Patients With Posner–Schlossman Syndrome - Liu, Dan; Fan, Cong; Zhang, Endong; Yang, Jie; Zhang, Yue; Jiang, Jian (Frontiers in Physiology, 2022)
Purpose: To evaluate the effect of intraocular pressure (IOP) reduction on macular and peripapillary microcirculation in patients with Posner-Schlossman syndrome (PSS) using optical coherence tomography angiography (OCTA). Methods: A prospective comparative study. Patients diagnosed with PSS at the Eye Center of Xiangya Hospital, Central South University from February 2020 to November 2021 were consecutively included. OCTA was used for the macular and peripapillary microcirculation measurements and optical coherence tomography (OCT) was used for the retinal nerve fiber layer (RNFL) and lamina cribiosa depth (LCD) measurements. Patients received OCT and OCTA examination at baseline and 1 week post-treatment when the IOP was under control . Changes in macular and peripapillary microcirculation, RNFL and LCD were calculated for all analyzed areas. Results: Twenty-one eyes from 21 patients were included in the study. Pre-treatment and post-treatment IOP was 43.17±10.36mmHg (ranged from 30mmHg to 60mmHg) and 17.17±2.85mmHg (ranged from 13mmHg to 23mmHg), respectively. No statistically significant changes were detected in RNFL, LCD or macular and peripapillary microcirculation after significant IOP reduction. Conclusions: The results suggested that large IOP reduction might not result in significant increase of peripapillary and macular capillary perfusion in patients with PSS.